2006 Canadian Conference on Electrical and Computer Engineering 2006
DOI: 10.1109/ccece.2006.277309
|View full text |Cite
|
Sign up to set email alerts
|

A Novel On-line Intelligent Shaft-Torsional Oscillation Monitor for Large Induction Motors and Synchronous Generators

Abstract: The paper presents a new method to detect subsynchronous resonance (SSR) -shaft torsional oscillation for large induction motors and synchronous generators. This is achieved by using a novel on-line Intelligent Shaft Monitor (ISM). The ISM device utilizes stator current and frequency based transformations. The proposed detection scheme is based on the stator current-excursion patterns and relevant phase-portraits. It can also be used to damp any SSR oscillation mode using a dynamic filter and static compensato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Sharaf and Azza Hassan (2006) showed that average yield of tomato grown on Alexandria in clay soils during the summer season were 24.19, 26.75 and 27.7 ton/feddan corresponding to water balance with Penman-Monteith, water balance with evaporation pan and tensiometers, respectively. The averages of applied irrigation water were 2130, 2340 and 2445 m3/fed for the same previous order.…”
Section: Introductionmentioning
confidence: 99%
“…Sharaf and Azza Hassan (2006) showed that average yield of tomato grown on Alexandria in clay soils during the summer season were 24.19, 26.75 and 27.7 ton/feddan corresponding to water balance with Penman-Monteith, water balance with evaporation pan and tensiometers, respectively. The averages of applied irrigation water were 2130, 2340 and 2445 m3/fed for the same previous order.…”
Section: Introductionmentioning
confidence: 99%